Effect of Drying Temperature on Sensory Properties of Mustard Flour (Brassica juncea) Using Oven Dryer - Yeny Ekawati; Ida Agustina Saidi (Procedia of Engineering and Life Science, 2021)
This study aims to determine the effect of drying temperatures on sensori properties of mustard greens flour. The study was conducted from February to April 2020. Hedonic test used non-parametric statistical to determine sensori properties of mustard greens flour.The sample used was mustard greens (Brassica juncea) from Waru, Sidoarjo. Various temperature used oven drying at 40oC, 50oC,60oC and 70oC. The results showed that the drying temperatures has not difference on hedonic test of color, aroma, and texture of mustard flour.